Analysis of Differences in Stock Returns Before and After the Fatwa of MUI in Indonesia on Israel Affiliated Companies - Setiawati, Ledy; Hidayati, Widya Nur (LP3M Universitas Putra Bangsa, 2024)
Stock return are defined as the excess of the selling price of a stock over its purchase price. The higher the selling price of the stock than the purchase price, the higher the return that will be obtained, and vice versa. There are several factors that affect stock returns, one of which is government or organization policy which is an external factor. The existence of MUI Fatwa Number 83 of 2023 and the BDS movement that occurred in Indonesia are thought to cause differences in returns on Israeli-affiliated companies. The Israeli-affiliated companies sampled in this study were 4 companies. The results of the study show that there is no difference in stock returns in 4 affiliated companies before and after the MUI Fatwa Number 83 of 2023.